Short video users’ personality traits and social sharing motivation - Da-yong, Zhang; Zhan, Su (Frontiers in Psychology, 2022)
Purpose/significance Studying the correlation between short video users’ personality traits and their sharing motivation can enrich the theoretical research on social sharing motivation and provide a reference for short-video content management and platform construction. Methods/process Based on uses and gratifications theory and personality traits theory, a structural model affecting short-video users’ sharing motivations was proposed. A total of 579 valid questionnaires were collected from a social network, and the proposed hypotheses were tested using SPSS and Amos software. Results/conclusion The results show that the personality traits of short-video users affect their sharing motivation and that their specific sharing motivation also differ due to their personality traits. At the same time, the research results also confirm the Matthew effect of “the rich getting richer” and the social compensation effect of “the poor getting richer” in the context of social platforms that host short videos.